Opportunities and limits of rebalancing the Eurozone via wage policies: Theoretical considerations and empirical illustrations for the case of Germany - Eckhard Hein; Eckhard Achim Truger (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2017)
In this paper we discuss the relationship between the current account rebalancing in the Eu-rozone, income distribution and wage policies with a focus on the main surplus economy, Germany. We will illustrate how and to which extent German wage policies could be able to contribute to a more balanced development of the Eurozone and to overcome the export-led mercantilist German model. Our analysis and our scenarios will be based on stylized econo-metric results for Germany, as they have recently been obtained in the empirical literature estimating the German demand and growth regime based on post-Kaleckian models. We will focus in particular on the relationship between nominal wages and functional income distribu-tion, on the one hand, and between functional income distribution and domestic demand, on the other hand. We show that more expansionary wage policy can contribute to reducing the excessive German current account surplus, mainly through the domestic income-imports channel. However, wage policy alone will be overburdened with the task of rebalancing. For this, in particular more expansionary fiscal policies are required.
Keywords: E21; E25; E27; E62; E64; F45; F47; H62; 330; Current account imbalances in the Eurozone; wage policies; distribution; exports; imports